Research Progress on Shallow Gas Exploration - Zhang, Chuanxiang; Guo, Xu; Yu, Ziwang (Journal of Progress in Civil Engineering, 2025)
Shallow gas is widely distributed across the globe, accounting for 20% of the total number of gas fields worldwide. By the end of 2005, it had accounted for 23% of the world’s proven recoverable natural gas reserves. As exploitable resources in the medium-deep layers decrease and the demand for natural gas extraction continues to rise, the development value of shallow gas and the significance of engineering risk prevention and control have become increasingly prominent. This study introduces the main exploration methods for shallow gas, including Cone Penetration Test (CPT), seismic exploration, electromagnetic exploration, and microbial exploration.